عالم ما بعد القطبية الأحادية الأمريكية – الصراع بين أمريكا وروسيا كقوة صاعدة - قنوع, نزار; قتابي, نور (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This paper attempts to discuss the issue of the future of the new international order that the analysts and thinkers, economists and politicians trying to find out his future after the end of the polar era of the one and the dominance of America to lead the world for a long period of time, and the emergence of new powers in the international arena began competing to lead the world, so we will discuss this issue through Three main themes are: first: polar constituents of American unilateralism, and the second: the challenges facing the Arctic American unilateralism, and the third: the only pole in the face of Russia (conflict of interest). Trying to figure out the future of the international system in the presence of these various forces. يحاول هذا البحث مناقشة مسألة مستقبل النظام الدولي الجديد الذي يحاول المحللين والمفكرين الاقتصاديين والسياسيين معرفة مستقبله بعد انتهاء عصر القطبية الواحدة وهيمنة أمريكا على قيادة العالم لمدة زمنية طويلة، وظهور قوى جديدة على الساحة الدولية بدأت تنافسها على قيادة العالم، لذلك سنبحث هذا الموضوع من خلال ثلاثة محاور رئيسية الأول: مقومات القطبية الأحادية الأمريكية، الثاني: التحديات التي تواجه القطبية الأحادية الأمريكية، والثالث: القطب الأوحد في مواجهة روسيا ( صراع المصالح ) في محاولة لمعرفة مستقبل النظام الدولي في ظل وجود هذه القوى المختلفة.